Odpowiedzi

Najlepsza Odpowiedź!
2009-11-20T08:07:51+01:00
(a+b)² = a² + 2ab + b²

(3x+2)² - (2-3x)²+(3x+2)(2-3x)=9x²+4+12x-(4+9x²-12x)+(4-9x²)=
9x²+4+12x-4-9x²+12x+4-9x²= 4+12x+12x-9x²= 4+24x-9x²

2(x-3y)² - 3(x-2y)(x+2y)+12xy = 2(x²+9y²-6xy)-3(x²-4y²)+12xy=
2x²+18y²-12xy-(3x²-12y²)+12xy = 2x²+18y²-12xy-3x²+12y²+12xy =
30y²-x²
1 5 1
2009-11-20T08:09:53+01:00
(a+b)(2)=a(2)+b(2) (2)-to potęga

(3x+2)(2)-(2-3x)(2)+(3x+2)(2-3x)=9x(2)+4-4+9x(2)+6x-9x(2)+4-6x=9x(2)+4

1 5 1
2009-11-20T08:12:07+01:00
(a+b)²=a²+2ab+b²

(3x+2)²-(2-3x)²+(3x+2)(2-3x)=(3x)²+2*3x*2+2²-(2²-2*2*3x)+6x²-9x²+4-6x=
=9x²+12x+4-(4-12x)-3x²+4-6x=9x²+12x+4-4+12x-3x²+4-6x=6x²+18x+4

2(3x-3y)²-3(x-2y)(x+2y)+12xy=2(9x²-18xy+9y²)-3(x²+2xy-2yx-4y²)+12xy=
=18x²-36xy+18y²-3x²-6xy+6yx+12y²+12xy=15x²-30xy+30y²+6yx
1 5 1